From a functional service to an emotional 'saviour': a structural analysis of logistics values for in-home consumers - Li, Ting (2024)
Logistics has been traditionally viewed as the movement of goods, but the stereotype of logistics as providing solely functional services is undergoing a transformation. Particularly for consumers with an in-home lifestyle, receiving logistics services is one of the effective ways to reaching out to the outside world when they are socially isolated. Therefore, this study aims to explore both the functional value and emotional value of logistics services. A synthesised theoretical framework is proposed which integrates the stimuli-organism-response model, affect transfer theory and logistics service quality model. A total of 632 valid responses were collected for data analysis. The results show that functional value (i.e., perceived service value) and emotional value (i.e., cognitive emotion regulation) jointly influence consumer satisfaction with logistics services. Furthermore, perceived service value is determined by response quality and order discrepancy handling quality, while cognitive emotional regulation is impacted by emotional attachment and self-control seeking. This research extends the scope of logistics research from functional to non-functional aspects by incorporating emotionally relevant factors in logistics services.